Analisis Layout Website Responsive Menggunakan Material Design Guidelines dan User Centered Design - Anggi Valeria Putri; Aryo Pinandito; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Differences in screen size between the desktop screen, tablet and smartphone and the diversity of the number of website columns cause the problem of decrease value effectiveness and efficiency of the website. This problem happens because the layout arrangement is less good when a website has a certain number of column conditions and transformed into a particular device. So it is necessary to rearrange a good website layout by adjusting the number of columns and certain devices. The layout arrangement consists of a website with the number of columns that is one column, two columns, and three columns and the device selected for layout arrangement is tablet and smartphone. The rearrangement of the website layout is derived from the application of Material Design Guidelines (MDG) and User Centered Design (UCD) approaches to find out which approach is better applied for layout arrangement with specific column counts and certain devices to improve the effectiveness and efficiency of the website. The equation of effectiveness and efficiency of Anton Sergeev (2010) is used to determine the increase or decrease in effectiveness and efficiency on website before and after modeled. Based on the results of this study, the MDG approach further increases the efficiency of website time of three columns tablet version. While UCD approach further increase the efficiency of website time one and two columns version of tablets and smartphones and three-column website version of the smartphone.